Performance-based optimal design of tuned impact damper for seismically excited nonlinear building. (1st April 2018) - Lu, Zheng; Li, Kun; Ouyang, Yuting; Shan, Jiazeng
Highlights: A real-world implementable design methodology for a Tuned impact damper (TID) system is introduced. A performance-based design method to obtain the optimal parameters of the TID system is proposed. An equivalent reduced-order model is developed to be used for the optimal TID parameter design. Optimal designed TID system significantly reduces structural damages compared with a conventional one. Abstract: This paper proposes a performance-based optimal design method for a tuned impact damper system, which is composed of a solid mass in a container and is located at the top of a 20-story complex nonlinear benchmark building of the third generation. This benchmark building is a steel frame, accounting for nonlinear response via material non-linearity (bi-linear hysteresis) concentrated at the ends of moment-resisting beam-column joints, and is designed for the SAC PhaseIIISteel Project. In order to illustrate the real-world implementable optimal design approach for designing an optimal tuned impact damper system attached to practical complex structures, a reduced-order data-driven physical model is developed by using the response data specifically from finite element model and the optimization-based parameter identification algorithm. The reduced-order model has been iteratively constructed to be consistent favorably with the finite element model on the aspects of both modal frequencies and mode shapes. Based on the reduced-order model, the optimal parameters of the tuned impact damper system are subsequently designed by adopting proposed performance indices and the differential evolution algorithm conveniently. The optimal vibration control effects are evaluated by using the original finite element model structure with the optimal tuned impact damper. Such optimal performance is also compared with that of the original finite element model with a conventionally designed tuned impact damper system. The results show that the optimal designed tuned impact damper system not only can significantly mitigate the peak and root mean square values of dynamic displacements, but also can reduce effectively the number of plastic hinges of the nonlinear benchmark structure compared with that with the conventional design. Furthermore, the performance-based optimal design can lead to a better robust performance of the tuned impact damper system in the cases of the main structure subjected to unknown earthquake excitations.